2020
DOI: 10.1177/2041731420934806
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness-matched biomaterial implants for cell delivery: clinical, intraoperative ultrasound elastography provides a ‘target’ stiffness for hydrogel synthesis in spinal cord injury

Abstract: Safe hydrogel delivery requires stiffness-matching with host tissues to avoid iatrogenic damage and reduce inflammatory reactions. Hydrogel-encapsulated cell delivery is a promising combinatorial approach to spinal cord injury therapy, but a lack of in vivo clinical spinal cord injury stiffness measurements is a barrier to their use in clinics. We demonstrate that ultrasound elastography – a non-invasive, clinically established tool – can be used to measure spinal cord stiffness intraoperatively in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…Clinical efficacy has not yet been achieved, and despite promising results in preclinical models, hydrogel scaffolds require further development as the mechanical properties have proven difficult to control. Researchers like Prager et al ( 182 ) have brought innovation to this area by reporting a protocol to determine a “target stiffness” for hydrogels, matched to the stiffness of the CNS, indicating development of the strategy for neural tissue repair. The application of electroactive hydrogel scaffolds and ES for SCI cell therapy, too, requires further development from the preclinical evidence gathered so far.…”
Section: Challenges For Nsc Transplantation In Scimentioning
confidence: 99%
“…Clinical efficacy has not yet been achieved, and despite promising results in preclinical models, hydrogel scaffolds require further development as the mechanical properties have proven difficult to control. Researchers like Prager et al ( 182 ) have brought innovation to this area by reporting a protocol to determine a “target stiffness” for hydrogels, matched to the stiffness of the CNS, indicating development of the strategy for neural tissue repair. The application of electroactive hydrogel scaffolds and ES for SCI cell therapy, too, requires further development from the preclinical evidence gathered so far.…”
Section: Challenges For Nsc Transplantation In Scimentioning
confidence: 99%
“…Stiffness refers to the ability of a material or structure to resist elastic deformation under stress. Many researchers have proposed a correlation between matrix stiffness and cellular behaviors after injury, disease, and cancer ( Wu et al, 2019 ; Kayal et al, 2020 ; Prager et al, 2020 ). Further studies confirmed that the stiffness of the cellular environment affects cell adhesion, proliferation, migration, differentiation, and phenotype.…”
Section: Regulation Of Physical Cues On Neuronal Behaviormentioning
confidence: 99%
“…Moreover, hydrogels can mimic the extracellular matrix (ECM) to provide a niche for cells, support the surrounding neural tissue and also act as a substrate for cell growth, neurite formation, and axon regeneration 10 . The high‐water content and porous inner structure help long‐term nutrient supply for cells and thus can aid in axon survival 13 . Numerous studies have indicated that hydrogels can promote cell adhesion, axon regeneration, and myelination in neural damage both in vitro and in vivo 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…10 The high-water content and porous inner structure help long-term nutrient supply for cells and thus can aid in axon survival. 13 Numerous studies have indicated that hydrogels can promote cell adhesion, axon regeneration, and myelination in neural damage both in vitro and in vivo. [14][15][16] Although hydrogelbased biomaterials possess superior biological properties, there are some drawbacks to natural hydrogels (such as collagen, fibrin, hyaluronic acid, and gelatin) as their mechanical properties are mostly dependent on polymerisation and the crosslinking mechanism and it can be difficult to control the microstructure and reproducibility between experiments.…”
mentioning
confidence: 99%